Kontribusi Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) dan Anggaran Pendapatan dan Belanja Daerah (APBD) Guna Mendukung Pelaksanaan Otonomi Daerah (Studi Kasus Pemerintah Daerah Kota Bogor) - Riduansyah, Mohammad (UI Scholars Hub, 2003)
The income of local own revenues is a significant sources for routine and developmen expenditure in local government. The amount of local taxation and user charges income are influenced by the kind of local taxation and user charges which is being implemented and adjusted by the rule that is implemented, related with income of local taxation and user charges. The contribution of local taxation and user charges income to acceptance of local own resources in Bogor Municipal in the periode of budget years 1993/1994-2000 has significant meaning with the average income 27,78 per years. The contributin of local taxation and user charges income to the total income of Bogor Municipal can be see in their local government budget, related to the ability in doing local authonomy is good enough. The component of local taxation in the period 1993/1994-2000 has contribute 7,81 % per years with the growth average about 22.89 % per years. Mean while, the acceptance that come form the user charge component, in the same periode has contributed 15,61 % per years with the growth average 5.08 % per years. In increasing the contribution of local taxation and user charge income to the total of local own resources income and their contribution to the local government budget of Bogor Municipal, several things need to be done, such as intensification of collecting local taxation and user charges and also extensification by implementation of new local taxation and user charge, adjusted with the condition and potention that available.